Development of Chemistry Tests for Students’ on Reaction Rate Subject Matter Based on Critical Thinking Skills using Framework DOT Test - Nurfatihah, Rahmawati; Nahadi, Nahadi; Firman, Harry (Journal of Educational Sciences, 2021)
This study aims to develop a valid and reliable test to measure the critical thinking skills of the high school students of class XI on reaction rate subject matter using the Danczak – Overton – Thompson test framework (DOT test). The research method used in this research is development and validation. In this article, there are three stages of test development, namely the analysis of KI and KD in Chemistry of 2013 curriculum, analysis of the DOT test framework, and the preparation of the test predictions. The development stages produce a draft instrument that is ready to be validated. The developed instrument consists of 30 test questions. The validation stage includes the content validity test by 5 expert judgments. In the validity test, the calculated CVI value is 0.97 so that the instrument is valid. Based on the analysis of research data, it is concluded that the chemistry test based on critical thinking skills that was developed had a good validity value to measure students' critical thinking skills on the reaction rate subject matter.